FATF AND PAKISTAN: ANALYZING QUESTION OF LEGITIMACY AND COMPLIANCE EFFORTS - Abdul Razzaq; Dr. Ataullah Khan Mahmood (International Journal of Contemporary Issues in Social Sciences, 2024)
The ongoing efforts to tackle Money Laundering via organizations like FATF and related mechanisms exhibit significant shortcomings. This is primarily due to the inherent issue of legitimacy that plagues FATF. Without addressing and safeguarding the fundamental rights enshrined by the United Nations through its declarations and upheld by the Constitution of the State, these endeavors fall short of achieving their intended objectives. Regarding the effectiveness of efforts to combat money laundering, particularly through organizations like the Financial Action Task Force (FATF). The main criticism revolves around the perceived lack of legitimacy within FATF and the failure to uphold fundamental rights as guaranteed by the UN and state constitutions. Money laundering is a global issue that requires coordinated efforts among nations. The text suggests that FATF and similar mechanisms might be flawed because they may not adequately prioritize human rights and may lack the necessary legitimacy to carry out their mission effectively. This is an important point to consider that how to improve anti-money laundering efforts, as it emphasizes the need to balance security concerns with the protection of rights, freedoms of States. Pakistan’s engagement with the Financial Action Task Force (FATF) is constrained by the factors of commitments, obligations, and challenges. In addition to Pakistan’s collaboration with the FATF on institutional measures, there is a pressing need to address operational measures, including the 27-point Action Plan mandated by the FATF for Pakistan. Given this context, comprehending the intricacies of combating Money Laundering and Terrorist Financing presents a formidable challenge for both Pakistan and the global community. Why Pakistan is entangled in a complex and seemingly biased framework of international regulations, and if so, how can it navigate this situation? What strategies can Pakistan employ to extricate itself from the FATF predicament? Notably, Pakistan has already outlined a narrative through its Combating the Financing of Terrorism (CFT) Regime and National Action Plan (NAP), emphasizing aspects related to terror financing, the leadership of terrorist organizations, and the role of Non-Governmental Organizations (NGOs).